Development and psychometric evaluation of a stakeholder perception scale of supervisors’ digital competencies for performance excellence (SDC-PE) - Ansar, Ansar; Arismunandar, Arismunandar; Rasdiana, Rasdiana; Ma’rifatin, Siti; Entrisnasari, Fantika Vera; Nindhiani, Rizqi (Frontiers in Education, 2026)
Despite growing interest in educational digital leadership and supervision, validated instruments measuring supervisors’ digital competencies for their performance excellence (SDC-PE) remain scarce, particularly in developing nations. This study developed and validated the SDC-PE scale through stakeholder perceptions of 318 principals and teachers across 78 senior high schools in 17 districts of South Sulawesi, Indonesia. The SDC-PE integrates classical supervision theories (Cogan, Goldhammer, Glickman) with ISTE Standards and DigCompEdu 2.2, yielding four dimensions: Strategic digital leadership (SDL), digital culture promotion (DGC), teacher digital development (TDD), and digital learning facilitation (DGL). Confirmatory composite analysis (CCA) using PLS-SEM demonstrated excellent psychometric properties: factor loadings (0.839–0.936), composite reliability (0.933–0.955), AVE (0.776–0.811), and model fit indices exceeding thresholds (CFI = 0.968, TLI = 0.960, RMSEA = 0.072). Discriminant validity was confirmed through Fornell-Larcker criterion and HTMT ratios (<0.85). The SDC-PE provides educational institutions with an empirically validated assessment tool for evaluating supervisor digital competencies, designing targeted professional development.